Anti-dazzle film for writing as well as preparation method and application of anti-dazzle film

By using the elastic layer with specific elastic modulus and microstructure in the anti -cooling membrane of the folding display device, the problem of poor writing feel in the existing technology has been solved, and a smoother writing experience and a higher impact resistance performance are achieved Essence

CN119375998APending Publication Date: 2025-01-28NINGBO HUGHSTAR ADVANCED MATERIAL TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411423911.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing transparent folding cover plate is prone to slip or pause when writing with a stylus, making the writing feel poor.

Method used

The anti-dizziness of the substrate layer layer and elastic layer is used. The elastic modulus of the elastic layer is 0.5-2GPa, the surface has a microstructure, the roughness is within the range of SA = 0.02-0.5 μm, and the sz = 0.5-3 μm. Through this structural design, control the damping when writing the handwriting pen, and enhance the writing touch.

Benefits of technology

Effectively enhance the writing touch, make the writing process smoother, reduce slipping and pause, while improving the anti -impact performance of the cover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119375998A_ABST
    Figure CN119375998A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides an anti-dazzle film for writing as well as a preparation method and application thereof, and relates to the field of protective films. The anti-dazzle film for writing comprises a base material layer and an elastic layer which are arranged in a stacked mode, the elastic modulus of the elastic layer is 0.5-2 GPa, the writing surface, away from the base material layer, of the elastic layer is provided with a microstructure, and the roughness of the writing surface of the elastic layer meets the conditions that Sa is 0.02-0.5 micrometer, and Sz is 0.5-3 micrometers. The anti-dazzle film for writing in the embodiment of the invention is applied as a protective film of folding display equipment. The anti-dazzle film for writing provided by the embodiment of the invention is good in writing touch feeling and can be applied to folding display equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of protective films, and in particular, to an anti-glare film for writing and a preparation method and application thereof. Background Art

[0002] With the rise of foldable display devices, the market demand for foldable cover panels is also growing. Currently, there are two main foldable cover panel technologies on the market, one is transparent polyimide film technology, and the other is ultra-thin glass technology. Both foldable cover panel technologies usually require a layer of transparent hardened coating on the surface to achieve anti-fouling and improve wear resistance, hardness and impact resistance. In addition, compared to straight-screen mobile phones, foldable display devices have powerful office functions and can generally replace computers for simple document editing, etc. Therefore, more and more foldable display devices will be equipped with stylus pens. However, when using a stylus to write on the surface of existing transparent foldable covers, they are prone to slipping or pausing, and the writing feel is not good. Summary of the invention

[0003] The purpose of the embodiments of the present application is to provide an anti-glare film for writing and a preparation method and application thereof, which has a good writing touch and can be applied to folding display devices.

[0004] In the first aspect, an embodiment of the present application provides an anti-glare film for writing, which includes a substrate layer and an elastic layer stacked together, the elastic modulus of the elastic layer is 0.5-2 GPa, the writing surface of the elastic layer away from the substrate layer has a microstructure, and the roughness of the writing surface of the elastic layer satisfies the conditions: Sa=0.02-0.5μm, Sz=0.5-3μm.

[0005] In the above technical solution, a microstructure with a certain roughness on the surface and an elastic layer with a certain elastic modulus are used to control the damping feeling when the stylus is writing, thereby improving the writing touch; in addition, the anti-glare film adopts an elastic layer, which can effectively absorb stress when falling or impacted by foreign objects, greatly improving the impact resistance of the cover.

[0006] Specifically, the writing damping feeling mainly depends on the friction between the writing pen tip and the cover surface (anti-glare film). The magnitude of the friction depends on two aspects: one is the contact area between the pen tip and the cover, and the other is the degree of sinking of the pen tip.

[0007] The elastic modulus of the elastic layer of the present application is 0.5-2GPa. If the modulus is too low, the sinking depth of the stylus tip is too large, and the damping feeling is too heavy. If the modulus is too high, the sinking depth of the stylus tip is insufficient, and it is easy to slip. If the modulus is too high, it will lead to insufficient impact resistance. This elastic layer has a large number of macromolecular linear structures, a low elastic modulus, and a large elastic deformation, which makes it easy to achieve the sinking of the pen tip. However, if the sinking degree is too large, it will cause the writing damping feeling to be too heavy and pause. The present application sets a microstructure on the surface of the elastic layer to reduce the contact area between the pen tip and the elastic layer, thereby reducing friction, reducing the damping feeling, and improving the writing touch.

[0008] By controlling the roughness of the writing surface, the elastic layer can have a suitable damping feeling to obtain the best writing experience. If the surface roughness of the writing surface is too small, the contact area between the stylus tip and the surface will be too large, and the damping feeling will be too heavy. If the surface roughness is too large, the friction between the surface and the stylus will be too small, and it will be easy to slip.

[0009] In a possible implementation, the substrate layer includes at least one of a transparent polyimide film, a polyethylene terephthalate film, an ultra-thin glass, a triacetate cellulose film, and an acrylic film;

[0010] The thickness of the substrate layer is 15-100 μm, and can be optionally 23-65 μm.

[0011] In a possible implementation, the material of the elastic layer includes at least one of polyurethane and polydimethylsiloxane;

[0012] The thickness of the elastic layer is 10-50 μm, and can be 15-30 μm.

[0013] In the above technical solution, the transparency of the substrate layer is good. If the thickness of the substrate layer is too thin, the support is insufficient. If the thickness is too thick, the overall thickness will be heavy and the bending performance will be reduced.

[0014] The elastic modulus of the elastic layer is low and the elastic deformation is large. If the thickness of the elastic layer is too thin, the writing damping feeling is insufficient and the impact resistance is insufficient. If the thickness is too thick, the writing damping feeling is too heavy.

[0015] In a possible implementation, the microstructure includes a concave space, and the shape of the concave space includes a single hemispherical shape and a clustered hemispherical shape.

[0016] In the above technical solution, the flash point problem is reduced by controlling the surface morphology of the microstructure.

[0017] In a possible implementation, the anti-glare film for writing satisfies at least one of the following conditions:

[0018] Haze is 1-30%;

[0019] Clarity ≥ 60%;

[0020] The bending performance meets R1mm≥200,000 times.

[0021] In the above technical solution, the optical performance requirements such as haze and clarity and the bending performance requirements are met.

[0022] In a second aspect, the present application provides a method for preparing the anti-glare film for writing according to the first aspect, which comprises the following steps:

[0023] coating an elastomer slurry on the substrate layer;

[0024] A microstructure is formed on the coating surface of the elastomer slurry by transfer printing, and the elastic layer is formed by curing.

[0025] In the above technical solution, the transfer technology is cleverly used to form a microstructure on the surface of the elastic layer.

[0026] In a possible implementation, the method for forming a microstructure includes the following steps:

[0027] A hardening liquid containing microspheres is coated on the base film and solidified to form a microstructure film having a transfer microstructure on the surface;

[0028] The microstructure film is covered on the coating surface of the elastomer slurry and rolled to replicate the transfer microstructure.

[0029] In the above technical solution, the transfer microstructure on the surface of the microstructure film is achieved by adding microspheres to the hardening liquid. The transfer method is to attach the microstructure film with the transfer microstructure to the coating of the elastomer slurry, and after roller pressing, the microstructure is transferred while the coating is cured to form an elastic layer.

[0030] In a possible implementation, the particle size of the microspheres is 1-7 μm, and can be 2-5 μm;

[0031] The transfer microstructure includes a single hemispherical protrusion and a cluster of hemispherical protrusions.

[0032] In the above technical solution, the microspheres may be one or more spherical particles. Spherical particles of different particle sizes and types may form different roughness of the transferred microstructures, and the roughness of the microstructures formed by the transfer is different.

[0033] In a possible implementation, the coating thickness of the hardening liquid is 1-5 μm, and can be 2-3 μm;

[0034] The water contact angle of the surface of the microstructure film having the transferred microstructure is ≥105°.

[0035] In a third aspect, an embodiment of the present application provides an application of the anti-glare film for writing according to the first aspect, wherein the anti-glare film for writing is used as a protective film for a folding display device.

[0036] In the above technical solution, an elastic layer with a microstructure is provided on the surface of the folding display device to control the writing damping feeling and improve the touch of the stylus. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 A schematic diagram of a preparation process of an anti-glare film for writing provided in an embodiment of the present application;

[0039] Figure 2 A schematic diagram of the preparation process of another anti-glare film for writing provided in an embodiment of the present application. DETAILED DESCRIPTION

[0040] When a stylus is used to write on the surface of the existing transparent folding cover, it is easy to slip or pause, and the writing touch is not good. In order to solve the problem of writing touch, some writing films are designed in the prior art.

[0041] One type of writing film has an elastic buffer layer added to the back of the writing layer. When the stylus passes through the writing layer, the pressure generated by the stylus acts on the elastic buffer layer through the writing layer, and the elastic buffer layer undergoes a sinking deformation similar to paper, giving the writer a paper-like writing experience. However, since the surface of the writing film has no structural design, it will completely contact the writing pen after being deformed by pressure, causing a sense of pause in writing, and the writing experience is still not good.

[0042] Another type of writing film is a matte writing film with a microstructure on the surface, but this writing film has a hard structure and no damping, so the writing experience is still not good and it has no impact resistance.

[0043] In addition, if ordinary AG handwriting film is directly used for folding cover, the resolution of the folding display device is too high, and the flash point problem will occur, and it will not be able to fold. The life of the folding cover is also the focus of consumers' attention. When a folding cover falls, it is easier to break than a straight cover.

[0044] Therefore, it is necessary to explore a writing film with a good writing experience, which can be applied to folding covers and meet usage requirements.

[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0046] The anti-glare film for writing according to the embodiment of the present application and its preparation method and application are described in detail below.

[0047] An embodiment of the present application provides an anti-glare film for writing, which includes a substrate layer and an elastic layer stacked together, the elastic modulus of the elastic layer is 0.5-2 GPa, the writing surface of the elastic layer away from the substrate layer has a microstructure, and the roughness of the writing surface of the elastic layer satisfies the conditions: Sa=0.02-0.5μm, Sz=0.5-3μm.

[0048] In the present application, Sa and Sz refer to indicators of surface roughness, Sa is the "arithmetic mean of the absolute values ​​of the profile deviations of all peaks and troughs" within the sampling area, and Sz is the "highest peak + lowest trough" within the sampling area.

[0049] The present application can effectively control the damping feeling within a suitable range and obtain the best writing experience by designing the roughness of the writing surface and the modulus of the elastic layer.

[0050] In some embodiments of the present application, the anti-glare film for writing satisfies at least one of the following conditions:

[0051] The substrate layer includes at least one of a CPI (transparent polyimide) film, a PET (polyethylene terephthalate) film, an UTG (ultra-thin glass), a TAC (cellulose triacetate) film, a PMMA (acrylic) film, and the like.

[0052] The thickness of the substrate layer is 15-100 μm, and can be optionally 23-65 μm;

[0053] The material of the elastic layer includes at least one of polyurethane and polydimethylsiloxane;

[0054] The thickness of the elastic layer is 10-50 μm, and optionally 15-30 μm.

[0055] In some embodiments of the present application, the microstructure includes a concave space, and the shape of the concave space includes a single hemispherical shape and a clustered hemispherical shape.

[0056] In some embodiments of the present application, the anti-glare film for writing satisfies at least one of the following conditions:

[0057] Haze is 1-30%;

[0058] Clarity (grating width 0.125mm) ≥ 60%;

[0059] The bending performance meets R1mm≥200,000 times.

[0060] Since the elastic layer has excellent optical properties such as haze and clarity, it does not affect the screen display effect. The haze and clarity of the anti-glare film are mainly determined by the microstructure. Therefore, by controlling the microstructure, the optical properties of the anti-glare film can be excellent and meet the use requirements. If the haze is too high or the clarity is too low, there will be serious flash point problems when applied to folding display devices. In addition, the elastic layer has excellent bending performance, and the anti-glare film formed meets the folding performance requirements of the folding display device. The bending performance of the elastic layer is controlled by its elastic modulus. The higher the elastic modulus, the worse the bending performance.

[0061] The present application also provides a method for preparing the anti-glare film for writing of the aforementioned embodiment, which comprises the following steps:

[0062] S1, coating the elastomer slurry on the substrate layer;

[0063] In some embodiments of the present application, the elastomer slurry is at least one of polyurethane elastomer slurry and polydimethylsiloxane elastomer slurry.

[0064] Exemplarily, the composition of the polydimethylsiloxane elastomer slurry includes: 70-110 parts by weight of polydimethylsiloxane oligomer, 7-12 parts by weight of curing agent, and 0.5-2 parts by weight of leveling agent, wherein the molecular weight of the polydimethylsiloxane oligomer is 2000-50000, optionally 5000-20000, and the viscosity is 500-20000cps, optionally 1000-10000cps; the curing agent can be a peroxide curing agent such as DBP, and the leveling agent is a silicone leveling agent.

[0065] Exemplarily, the composition of the polyurethane elastomer slurry includes: 60 parts by weight of polyurethane oligomer, 40 parts by weight of organic solvent, wherein the molecular weight of the polyurethane oligomer is 1000-30000, optionally 2000-10000, and the viscosity is 100-20000 cps, optionally 200-5000 cps.

[0066] In some embodiments of the present application, the coating thickness of the elastomer slurry is 10-50 μm, and can be optionally 15-30 μm. If the coating thickness is too thin, the writing damping feeling is insufficient and the impact resistance is insufficient. If the coating thickness is too thick, the writing damping feeling is too heavy.

[0067] S2. Forming a microstructure on the coating surface of the elastomer slurry by transfer printing, and curing to form an elastic layer.

[0068] In some embodiments of the present application, the method for forming a microstructure comprises the following steps:

[0069] S21. Apply a hardening liquid containing microspheres on the base film, and solidify it to form a microstructure film with a transfer microstructure on the surface.

[0070] It should be noted that the roughness of the writing surface of the elastic layer is controlled by the microstructure film. The roughness of the writing surface of the elastic layer is the same as that of the microstructure film, so the roughness of the microstructure film is also Sa = 0.02-0.5μm, Sz = 0.5-3μm. The microstructure of the writing surface of the elastic layer and the transfer microstructure of the surface of the microstructure film are in a matching relationship. Accordingly, the transfer microstructure includes a single hemispherical protrusion and a cluster of hemispherical protrusions. It can contain two microstructure forms, which can be a single hemispherical structure or a hemispherical aggregate.

[0071] The microspheres may be a mixture of one or more spherical particles of a single particle size, and the material may be one or more of silica, PMMA, PS, copolymers, etc. In some embodiments of the present application, the particle size D50 of the microspheres is 1-7 μm, and may be optionally 2-5 μm. If the particle size is too small, the writing surface roughness formed by the transfer is too small, and if the particle size is too large, the writing surface roughness formed by the transfer is too large, and the flash point on the screen seriously affects the display effect.

[0072] In some embodiments of the present application, the coating thickness of the hardening liquid is 1-5 μm, optionally 2-3 μm;

[0073] The water contact angle of the surface of the microstructured film with the transferred microstructure is ≥105°. The specific water contact angle is to ensure that the microstructured film is smoothly and completely peeled off from the surface of the elastic layer. If the water contact angle is too small, the film cannot be peeled off or the peeling is incomplete.

[0074] S22, covering the microstructure film on the coating surface of the elastomer slurry, and rolling to replicate the transfer microstructure.

[0075] The present application adopts a transfer peeling method to form the microstructure of the elastic layer, which is specifically obtained by surface transfer and peeling of a microstructure film with a transfer microstructure. Compared with the roller embossing method, this method is low-cost, efficient, and flexible, while the roller mold opening cost is high and the structure cannot be adjusted after the mold opening. In addition, this method has no restrictions on the curing method of the coating, while the roller embossing method must be a light-curing method.

[0076] Figure 1 This is a schematic diagram of the preparation process of an anti-glare film for writing. The transferred microstructure of the microstructure film is a single hemispherical protrusion, and the microstructure formed on the surface of the elastic layer is a single hemispherical concave space.

[0077] Figure 2 This is a schematic diagram of the preparation process of another anti-glare film for writing. The transferred microstructure of the microstructure film is clustered hemispherical protrusions, and the microstructure formed on the surface of the elastic layer is a clustered hemispherical concave space.

[0078] As an embodiment, the process of preparing the microstructured film is as follows:

[0079] S211. Prepare a hardening liquid containing microspheres.

[0080] S2111. Weigh 40-60 parts by weight of polyurethane acrylate oligomer, add 45-50 parts by weight of organic solvent, 2-3 parts by weight of photoinitiator, and 0.3-0.7 parts by weight of leveling agent, stir evenly to obtain clear solution A.

[0081] Among them, the functionality of the polyurethane acrylate oligomer can be 6-30, and can be optionally 6-15; the organic solvent can be commonly used organic solvents such as ethyl acetate, butanone, butyl acetate, propylene glycol methyl ether, etc.; the photoinitiator can be commonly used photoinitiators such as PI184, PI819, TPO, etc.; the leveling agent can be a perfluoropolyether rheological additive.

[0082] S2112, weigh 7-15 parts by weight of microspheres, add 7-15 parts by weight of dispersant, add 60-100 parts by weight of organic solvent, stir evenly, and obtain slurry B.

[0083] The microspheres may be a mixture of one or more spherical particles of a single particle size, and the material may be one or more of silica, PMMA, PS, copolymers, etc.; the dispersant may be a high molecular weight polyether dispersant.

[0084] S2113. Weigh 40-60 parts by weight of clear liquid A, add 2.5-25 parts by weight of slurry B, and add 25-47.5 parts by weight of organic solvent to obtain a hardening liquid containing microspheres.

[0085] S212, coating the hardening liquid on the surface of the base film, drying the solvent in an oven, and then UV curing to obtain a microstructure film.

[0086] It should be noted that, in the present application, the elastic layer can also be disposed on the surface of the substrate layer by lamination or the like.

[0087] The present application also provides an application of the anti-glare film for writing of the aforementioned embodiment, and the anti-glare film for writing is used as a protective film for a folding display device. Specifically, the anti-glare film for writing can be directly used as a folding cover plate to protect the folding display device; the anti-glare film for writing can also be used as a protective film attached to the surface of the folding cover plate to protect the folding display device.

[0088] The features and performance of the present application are further described in detail below in conjunction with the embodiments.

[0089] Example 1

[0090] This embodiment provides an anti-glare film, and the preparation process thereof is as follows:

[0091] (1) Preparation of microstructured films:

[0092] Weigh 25 parts by weight of polyurethane acrylate oligomer, add 23.5 parts by weight of organic solvent, 1.25 parts by weight of photoinitiator, and 0.25 parts by weight of leveling agent, and stir at 500 rpm for 30 minutes to obtain a clear solution A;

[0093] Weigh 2.5 parts by weight of microspheres, add 2.5 parts by weight of dispersant, add 20 parts by weight of organic solvent, and stir at 2000 rpm for 30 min to obtain slurry B.

[0094] The clear solution A is added to the slurry B and 25 parts by weight of an organic solvent to obtain a hardened solution containing microspheres.

[0095] The hardening coating liquid is coated on the surface of the PET film, the solvent is dried in an oven, and then UV-cured to obtain a microstructured film.

[0096] (2) Prepare polydimethylsiloxane elastomer slurry:

[0097] 90 parts by weight of polydimethylsiloxane oligomer were weighed, 9 parts by weight of curing agent and 1 part by weight of organic silicone leveling agent were added, and the mixture was stirred at 500 rpm for 30 minutes to obtain polydimethylsiloxane elastomer slurry.

[0098] (3) The above elastomer slurry is coated on a foldable transparent substrate, and a microstructure film is covered on the coating of the elastomer slurry. After being pressed by a laminating roller, it is placed in an oven and baked at 100° C. for 30 minutes for curing, and then baked at 40° C. for 2 hours to fully cure and cross-link it. After curing, the microstructure film is peeled off.

[0099] Examples 2-6 and Comparative Examples 1-8 respectively provide an anti-glare film. The specific formulations of Examples 1-6 and Comparative Examples 1-8 are shown in Table 1 below, wherein the main difference between Example 3 and Example 1 in terms of steps is:

[0100] (2) Prepare polyurethane elastomer slurry:

[0101] 60 parts by weight of polyurethane resin were weighed, 40 parts by weight of organic solvent were added, and the mixture was stirred at 500 rpm for 30 minutes to obtain polyurethane elastomer slurry.

[0102] (3) The above elastomer slurry is coated on the foldable transparent substrate to form a film, and then the microstructure film is covered on the elastic layer. The solvent is evaporated after baking at 100° C. for 10 minutes, and the microstructure film is peeled off after curing.

[0103] Table 1 Formula composition of embodiments and comparative examples

[0104]

[0105]

[0106] In Table 1, the raw materials for forming clear liquid A are: the acrylate oligomer is acrylate oligomer Kyoeisha 306T, which is a polyurethane acrylate hyperbranched oligomer with a functionality of 9, a molecular weight of 2000, and a solid content of 100%; the photoinitiator is photoinitiator 184; the leveling agent is Kaihong DAU3000, a perfluoropolyether reactive rheological additive; and the solvent is BAC:MEK=1:1.

[0107] The raw materials for forming slurry B: spherical particles are Nippon Shokubai SS2 (PS particles, monodisperse, particle size 0.2 μm), Sekisui Chemical SSX-101 (PMMA particles, monodisperse, particle size 1 μm), SSX-102 (PMMA particles, monodisperse, particle size 2 μm), SSX-103 (PMMA particles, monodisperse, particle size 3 μm), SSX-105 (PMMA particles, monodisperse, particle size 5 μm), SSX-108 (PMMA particles, monodisperse, particle size 8 μm), Suzhou Jinyi D200 (silicon dioxide, monodisperse, particle size 2 μm), Evonik OK607 (silicon dioxide, amorphous, particle size 4.5 μm); the dispersant is BASF 4310.

[0108] The raw materials for forming the elastomer slurry: polydimethylsiloxane oligomer and curing agent C-100 are from Hangzhou Weisi, polydimethylsiloxane oligomer, modulus 0.6 GPa, solid content 100%; curing agent is DBP, and leveling agent is BYK3550.

[0109] The polydimethylsiloxane oligomer and curing agent C-150 are from Hangzhou Weisi, polydimethylsiloxane oligomer, modulus 2GPa, solid content 100%; the curing agent is DBP, and the leveling agent is BYK3550.

[0110] The polydimethylsiloxane oligomer and curing agent TSR9002 are from Momentive, polydimethylsiloxane, modulus 3GPa, solid content 100%, curing agent is DBP, and leveling agent is BYK3550.

[0111] The polyurethane resin KRF01 is Suzhou Kangjingsi TPU resin with a modulus of 0.2GPa.

[0112] The polyurethane resin KRF03 is Suzhou Kangjingsi TPU resin with a modulus of 1.2GPa.

[0113] The foldable transparent substrate may be CPI, C50, manufactured by KOLON Corporation, with a thickness of 50 μm.

[0114] The foldable transparent substrate can be UTG, UTG30, Changxin Technology, with a thickness of 30μm.

[0115] The above anti-glare film is tested in the following manner:

[0116] 1. Elastic layer thickness test method:

[0117] Use a micrometer thickness gauge, first calibrate the instrument to zero, then place the film flat on the test position, and then use a micrometer to measure the film thickness. Subtract the thickness of the foldable transparent substrate layer 50μm from the measured film thickness to get the thickness of the elastic layer.

[0118] 2. Elastic layer roughness test method:

[0119] The test was carried out using a laser confocal microscope. The microstructure elastic layer was placed face up and the film was kept flat. A 20x objective was used for observation. After focusing on the upper surface, laser measurement was used. After measurement, the surface roughness Sa and Sz were calculated.

[0120] 3. Haze test:

[0121] Use NDH2000N haze meter to test. Calibrate first, then cut the sample into 5*5cm square, put it into NDH2000N haze meter, click test, and record the result.

[0122] 4. Clarity test:

[0123] Use SUGA ICM-1T to test. Calibrate first, then cut the sample into a 5*5cm square, put it into the clarity meter, click test, and record the results.

[0124] 5. Bending test:

[0125] Set the bending radius to 1mm, the test frequency to 40 times / min, the test times to 5 / 10 / 15 / 200,000 times, fix the sample on the test platform, pay attention to the bending direction, remove the sample after the test, and observe it. If there is no whitening or cracks, it is considered to have passed.

[0126] 6. Flash point test:

[0127] Use screens with different resolutions for testing. Use OCA to stick the sample on screens with different resolutions. Adjust the screen to a pure bright green background. Observe the flash point and record the maximum resolution value without obvious flash point.

[0128] 7. Damping test:

[0129] Fix the magic pencil on the damping tester for testing, and record the level at which it starts to slide. The larger the level, the heavier the damping. Levels 1-3 are too small and writing will cause slippage. Levels 4-7 are moderate and provide the best writing experience. Levels 8-10 are too large.

[0130] 8. Pen test:

[0131] Fix the sample on the drop tester, drop the pen from different heights, and record the highest number of meters at which the sample is damaged.

[0132] The test results are shown in Table 2 below:

[0133] Table 2 Performance test results

[0134]

[0135]

[0136] According to the above results, we can know that:

[0137] It can be seen from the results of Examples 1-6 and Comparative Examples 1-5 that the writing damping feeling can be controlled within an appropriate range by providing a microstructure with a certain roughness on the elastic layer.

[0138] It can be seen from the results of Comparative Examples 1 and 2 and Example 1 that if the microstructure roughness is too small, the damping feeling will be too heavy, affecting the writing experience.

[0139] From the results of Comparative Examples 3, 4, 5 and Example 4, it can be seen that if the microstructure roughness is too large, the damping feeling is too small, the writing is slippery, and if the roughness is too large, the flash point is serious, which affects the display effect.

[0140] It can be seen from the results of Example 2 and Comparative Example 6 that when the surface microstructure is the same, the higher the elastic layer modulus, the smaller the damping feeling. If the elastic layer modulus is too high, the writing effect will be affected. When the elastic layer modulus is too high, the bending performance and impact resistance will decrease.

[0141] It can be seen from the results of Example 3 and Comparative Example 7 that when the surface microstructure is the same, the lower the modulus of the elastic layer, the greater the damping feeling. Too low a modulus of the elastic layer will also affect the writing experience.

[0142] From the results of Example 2 and Comparative Example 8, it can be seen that when the surface microstructure is the same, the thinner the elastic layer thickness is, the smaller the damping feeling is, which affects the writing effect, and when the elastic layer thickness is too thin, the impact resistance effect decreases. In addition, the particle size and particle addition amount in the microstructure film formula will affect the size and density of the microstructure, and thus affect the clarity of the anti-glare film.

[0143] In summary, the anti-glare film for writing and the preparation method and application thereof of the embodiments of the present application have a good writing touch and can be applied to folding display devices.

[0144] The above description is only an embodiment of the present application and is not intended to limit the protection scope of the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An anti-glare film for writing, characterized in that: It includes a substrate layer and an elastic layer stacked together, the elastic modulus of the elastic layer is 0.5-2GPa, the writing surface of the elastic layer away from the substrate layer has a microstructure, and the roughness of the writing surface of the elastic layer meets the conditions: Sa=0.02-0.5μm, Sz=0.5-3μm.

2. The anti-glare film for writing according to claim 1, characterized in that: The substrate layer includes at least one of a transparent polyimide film, a polyethylene terephthalate film, an ultra-thin glass, a triacetate cellulose film, and an acrylic film; The thickness of the substrate layer is 15-100 μm, and can be optionally 23-65 μm.

3. The anti-glare film for writing according to claim 1, characterized in that: The material of the elastic layer includes at least one of polyurethane and polydimethylsiloxane; The thickness of the elastic layer is 10-50 μm, and can be 15-30 μm.

4. The anti-glare film for writing according to claim 1, characterized in that: The microstructure includes a concave space, and the shape of the concave space includes a single hemispherical shape and a clustered hemispherical shape.

5. The anti-glare film for writing according to claim 1, characterized in that: The anti-glare film for writing satisfies at least one of the following conditions: Haze is 1-30%; Clarity ≥ 60%; The bending performance meets R1mm≥200,000 times.

6. A method for preparing an anti-glare film for writing according to any one of claims 1 to 5, characterized in that: It includes the following steps: coating an elastomer slurry on the substrate layer; A microstructure is formed on the coating surface of the elastomer slurry by transfer printing, and the elastic layer is formed by curing.

7. The method for preparing an anti-glare film for writing according to claim 6, characterized in that: The method of forming the microstructure comprises the following steps: A hardening liquid containing microspheres is coated on the base film and solidified to form a microstructure film having a transfer microstructure on the surface; The microstructure film is covered on the coating surface of the elastomer slurry and rolled to replicate the transfer microstructure.

8. The method for preparing an anti-glare film for writing according to claim 7, characterized in that: The particle size of the microspheres is 1-7 μm, and can be 2-5 μm; The transfer microstructure includes a single hemispherical protrusion and a cluster of hemispherical protrusions.

9. The method for preparing an anti-glare film for writing according to claim 7, characterized in that: The coating thickness of the hardening liquid is 1-5 μm, and can be 2-3 μm; The water contact angle of the surface of the microstructure film having the transferred microstructure is ≥105°.

10. Use of the anti-glare film for writing according to any one of claims 1 to 5, characterized in that: The anti-glare film for writing is used as a protective film for a folding display device.